Odpowiedzi

  • kan
  • Początkujący
2009-10-22T17:02:31+02:00
A) -7(x+2)+4=-3x
-7x+(-14)+4=-3x
-7x+3x=-4+14
-4x=10/:(-4)
x=¹⁰/₋₄
x=-2²/₄=-2¹/₂

b) 1-2x+5÷3=4
-2x+⁵/₃=4-1
-2x=3-⁵/₃
-2x=⁹/₃-⁵/₃
-2x=⁹⁻⁵/₃
-2x=⁴/₃ /:(-2)
x=⁴/₃:(-²/₁)
X=⁴/₃×(-¹/₂)
x=-⁴/₆=-²/₃

c) -4(½×-2)-4=2(-×+2)
-⁴/₂x+8-4=-2x+4
-2x+2x=4-8+4
0=0

d) 2x(x-1)=2(x-1)(x+3)
2x²-2x=2(x²-3)
2x²-2x=2x²-6
2x²-2x-2x²=6
-2x=6 /:(-2)
x= ⁶/₋₂=-3

e) x/2-x/3+1=1/6(x+6)
x/₂-x/₃+1=¹/₆x+⁶/₆
x/₂-x/₃=¹/₆x+1-1
3x-2x/₆=¹/₆x
x/₆=¹/₆x /×6
6x/6=6/6x
x=x
tego nie jestem pewien reszta jest ok powodzenia